A lifestyle change, not a forever diet: one service user's experience of accessing a local health trainer service - Scurr, Carol (The journal of the Royal Society for the Promotion of Health)
[...]the whole family is food obsessed. In the past, my general practitioner (GP) told me I was overweight and gave me a little bit of information about healthy eating; but nothing like the in-depth, personalised advice I have received from the health trainer service.